2020
DOI: 10.3390/vaccines8040673
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Proteins Induce IFNG in Th1 Lymphocytes Generated from CD4+ Cells from Healthy, Unexposed Polish Donors

Abstract: The outbreak of the SARS-CoV-2 virus in December 2019 has caused the deaths of several hundred thousand people worldwide. Currently, the pathogenesis of COVID-19 is poorly understood. During the course of COVID-19 infection, many patients experience deterioration, which might be associated with systemic inflammation and cytokine storm syndrome; however, other patients have mild symptoms or are asymptomatic. There are some suggestions that impaired cellular immunity through a reduction in Th1 response and IFNG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Therefore, it can be concluded that Th1 cells increase inflammation in patients with COVID-19 by INF-γ production. Consistent with these results, it has been reported that the SARS-CoV-2 virus induces polyclonal Th1 cells, that the rate of these responses varies from patient to patient based on the immune system status and history of the underlying disease [45] . In another study, Elizaldi and colleagues indicated that Th1 cell responses dramatically increased after infection with the SARS-CoV-2 virus [46] .…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it can be concluded that Th1 cells increase inflammation in patients with COVID-19 by INF-γ production. Consistent with these results, it has been reported that the SARS-CoV-2 virus induces polyclonal Th1 cells, that the rate of these responses varies from patient to patient based on the immune system status and history of the underlying disease [45] . In another study, Elizaldi and colleagues indicated that Th1 cell responses dramatically increased after infection with the SARS-CoV-2 virus [46] .…”
Section: Discussionsupporting
confidence: 81%
“…However, it should be noted that we have no direct evidence that this is the case and further research is required. Interestingly, the SARS-CoV-2 S protein also showed an activating effect on cytokine expression in Th1 cells [ 27 ]. However, in contrast to monocytes, which showed a higher response to the SARS-CoV-2 N protein ( Figure 2 A), Th1 cells did not show such a preference [ 27 ], which is somewhat contradictory to the results of a bioinformatics study by Dhall et al [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the SARS-CoV-2 S protein also showed an activating effect on cytokine expression in Th1 cells [ 27 ]. However, in contrast to monocytes, which showed a higher response to the SARS-CoV-2 N protein ( Figure 2 A), Th1 cells did not show such a preference [ 27 ], which is somewhat contradictory to the results of a bioinformatics study by Dhall et al [ 41 ]. This observation might be of importance in the context of developing vaccines based on SARS-CoV-2 proteins, as it suggests that SARS-CoV-2 N protein-based vaccines might be more likely to induce a Th2 immune response, leading to humoral immunity, than vaccines utilizing the SARS-CoV-2 S protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SARS-CoV-2 infected patients, cytokine storm has been reported in which there are massive increases in inflammatory cytokines, such as, interleukins, TNF, colony stimulating factors (CSFs), and growth factors (GFs). Emerging evidence suggests the involvement of epigenetic modifications in these increases [ 249 , 250 ]. Variable response of individuals infected with SARS-CoV-2 could possibly be influenced by epigenetic regulators of cytokines, as has been reported in lupus patients [ 187 ].…”
Section: Epigenetic Regulation Of Inflammationmentioning
confidence: 99%